Managing cross-cultural communication - Maude, Barry (Palgrave Macmillan, 2011)
Includes bibliographical references and index; Machine generated contents note: -- PART ONE: PRINCIPLES -- What is Culture? Culture Values in business and society -- Language Matters -- Nonverbal aspects of cross-cultural communication -- Prejudice and Stereotypes -- PART TWO: PRACTICE -- Expatriate performanceCross-cultural adjustmentDeveloping cross-cultural skillsCommunicating across the cultural distanceManaging and working in multicultural teamsCross-cultural meetings and negotiationsCross-cultural interviews and selection